Identifying the most appropriate expansion of acronyms used in wikipedia text. (6th November 2014) - Choi, Dongjin; Kim, Pankoo; You, Ilsun; Ogiela, Marek R.; Hwang, Myunggwon
Summary During the past several years, many studies have been conducted to determine the expansions (the expanded forms or definitions) of acronyms used in specific texts by using linguistic and syntactical approaches to overcome disambiguation problems. An acronym is an abbreviation formed of the initial components of multiple words. Using only these initial parts can result in huge mistakes when a machine conducts experiments to determine an acronym's meaning in given texts. Finding expansions of acronyms is currently not a major concern. However, identifying how a polysemous acronym is precisely being used in a specific text is difficult. To solve disambiguation problem acronyms have, this paper proposes a method to identify the most appropriate expansions of an acronym by analysing co‐occurrence words found in articles on Wikipedia. Our goal is not to find an acronym's definition or expansion but to identify the most appropriate expansion of a given acronym as it is used in a given text. Through experiments, we demonstrate the proposed method's efficiency and performance by comparing several results. Copyright © 2014 John Wiley & Sons, Ltd.